Impact of renewable intermittency on brazilian smart grids - Martins, Maria Eduarda; Rafael; Ferraz, Renato (Latin American Journal of Energy Research, 2026)
The growing penetration of intermittent renewable energy sources, particularly solar photovoltaic and wind generation, has significantly transformed the Brazilian electricity matrix and the operational dynamics of the power system. Although essential for advancing decarbonization and meeting climate targets, these technologies introduce substantial challenges to the stability, predictability, and operational flexibility of smart grids. This article investigates, through an integrative literature review, case study analyses, and a comparison of national and international experiences, the technical, regulatory, and operational effects associated with intermittency in the Brazilian context. The results highlight the need to expand solutions such as multi-scale energy storage systems, advanced weather forecasting models based on artificial intelligence, active demand response mechanisms, and increased infrastructure digitalization. Despite the progress achieved, regulatory barriers, institutional constraints, governance challenges, and technological gaps still hinder the full integration of these resources. Finally, the study proposes guidelines for strengthening the regulatory framework, modernizing the grid, improving planning and operational criteria, and advancing workforce training, establishing essential foundations for an intelligent, resilient, and secure energy transition in Brazil.
Keywords: Energy planning; intermittency; operation; renewable sources; smart grids.